Climate change impacts and adaptation in South Africa. (3rd July 2014) - Ziervogel, Gina; New, Mark; Archer van Garderen, Emma; Midgley, Guy; Taylor, Anna; Hamann, Ralph; Stuart‐Hill, Sabine; Myers, Jonny; Warburton, Michele
<x xml:space="preserve">Abstract</x> In this paper we review current approaches and recent advances in research on climate impacts and adaptation in South Africa. South Africa has a well‐developed earth system science research program that underpins the climate change scenarios developed for the southern African region. Established research on the biophysical impacts of climate change on key sectors (water, agriculture, and biodiversity) integrates the climate change scenarios but further research is needed in a number of areas, such as the climate impacts on cities and the built environment. National government has developed a National Climate Change Response White Paper, but this has yet to translate into policy that mainstreams adaptation in everyday practice and longer‐term planning in all spheres and levels of government. A national process to scope long‐term adaptation scenarios is underway, focusing on cross‐sectoral linkages in adaptation responses at a national level. Adaptation responses are emerging in certain sectors. Some notable city‐scale and project‐based adaptation responses have been implemented, but institutional challenges persist. In addition, a number of knowledge gaps remain in relation to the biophysical and socio‐economic impacts of climate change. A particular need is to develop South Africa's capacity to undertake integrated assessments of climate change that can support climate‐resilient development planning. WIREs Clim Change 2014, 5:605–620. doi: 10.1002/wcc.295 For further resources related to this article, please visit the WIREs website. Conflict of interest: The authors have declared no conflicts of interest for this article.